2022
DOI: 10.3390/biomedicines10010156
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in microRNA Genes and Colorectal Cancer Risk and Prognosis

Abstract: There is growing interest in single nucleotide polymorphisms (SNPs) in the genes of microRNAs (miRNAs), which could be associated with susceptibility to colorectal cancer (CRC) and therefore for prognosis of the disease and/or treatment response. Moreover, these miRNAs-SNPs could serve as new, low-invasive biomarkers for early detection of CRC. In the present article, we performed a thorough review of different SNPs, which were investigated for a correlation with the CRC risk, prognosis, and treatment response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 127 publications
2
15
0
Order By: Relevance
“…The pro‐inflammatory nature of prognosis is related to the pathogenesis of many chronic inflammatory diseases 17,18 . Therefore, the inflammatory microenvironment formed by the release of a large number of inflammatory factors in the process of prognosis may promote the occurrence and development of tumors 16 . Our results also showed that polysaccharide of L. casei SB27 suppressed IL‐6, IL‐17a, ptgs2 mRNA expressions in mice model of colon cancer.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The pro‐inflammatory nature of prognosis is related to the pathogenesis of many chronic inflammatory diseases 17,18 . Therefore, the inflammatory microenvironment formed by the release of a large number of inflammatory factors in the process of prognosis may promote the occurrence and development of tumors 16 . Our results also showed that polysaccharide of L. casei SB27 suppressed IL‐6, IL‐17a, ptgs2 mRNA expressions in mice model of colon cancer.…”
Section: Discussionmentioning
confidence: 50%
“…The occurrence and development of tumors are determined by many factors, including the relative activity of proto oncogenes and tumor suppressor genes, immune microenvironment, and inflammatory microenvironment 16 . The pro‐inflammatory nature of prognosis is related to the pathogenesis of many chronic inflammatory diseases 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…The SNP sites located in the seed region of miRNAs can prevent the binding of miRNAs to target genes, resulting in increased expression of diseaserelated genes. [39][40][41] The SNP sites in the lncRNA sequence can damage the binding of protein to the lncRNA, resulting in the abnormal activity of the promoter that is lncRNA-mediated, and then induce the disordered expression of the target gene. 30,[42][43][44] Last but not the least, SNP mutations can destroy the expression of genes by altering the structures of topologically associating domains (TADs) [45][46][47][48] or disrupting tandem repeats.…”
Section: The Roles Of Snps Inside the Regulatory Elementsmentioning
confidence: 99%
“…SNP mutations occur not only in the binding region of miRNA but also in the seed region of miRNA itself. The SNP sites located in the seed region of miRNAs can prevent the binding of miRNAs to target genes, resulting in increased expression of disease‐related genes 39–41 . The SNP sites in the lncRNA sequence can damage the binding of protein to the lncRNA, resulting in the abnormal activity of the promoter that is lncRNA‐mediated, and then induce the disordered expression of the target gene 30,42–44 .…”
Section: The Roles Of Snps Inside the Regulatory Elementsmentioning
confidence: 99%
“…5 Recent evidence suggests that miRNAs may also be involved in tumor development by critically regulating CSCs. 9,10 This study aimed to determine the expression profiles of miRNAs in CSC-positive and early-stage CC patients and to examine their associations with recurrence formation. The identification of patients with a high risk of dissemination in this subset may optimize the use of adjuvant therapies.…”
Section: Introductionmentioning
confidence: 99%